2017
DOI: 10.1038/s41598-017-07839-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastin deletion in glutamatergic neurons impairs selective brain functions and calcium regulation: implication for cognitive deterioration

Abstract: The cell adhesion molecule neuroplastin (Np) is a novel candidate to influence human intelligence. Np-deficient mice display complex cognitive deficits and reduced levels of Plasma Membrane Ca2+ ATPases (PMCAs), an essential regulator of the intracellular Ca2+ concentration ([iCa2+]) and neuronal activity. We show abundant expression and conserved cellular and molecular features of Np in glutamatergic neurons in human hippocampal-cortical pathways as characterized for the rodent brain. In Nptn lox/loxEmx1Cre m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
93
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(103 citation statements)
references
References 62 publications
9
93
1
Order By: Relevance
“…Human Np65 was found to specifically localize on the neuronal membranes and in neuropil, while the overall Np immunoreactivity is distributed throughout distinct neuron‐containing hippocampal sublayers in both AD and control hippocampi (Figure ). The highest Np signal in normal human hippocampus is present in the CA1 area and dentate gyrus, > CA2/3, > hilus, > subiculum, and is specifically expressed in sublayers containing pyramidal or granule cells, as reported previously …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Human Np65 was found to specifically localize on the neuronal membranes and in neuropil, while the overall Np immunoreactivity is distributed throughout distinct neuron‐containing hippocampal sublayers in both AD and control hippocampi (Figure ). The highest Np signal in normal human hippocampus is present in the CA1 area and dentate gyrus, > CA2/3, > hilus, > subiculum, and is specifically expressed in sublayers containing pyramidal or granule cells, as reported previously …”
Section: Resultssupporting
confidence: 81%
“…Studies in literature have indicated multiple different (patho)physiological functions of cell‐adhesion molecule (CAM) neuroplastin in the human brain such as: the association of neuroplastin gene polymorphisms with cognitive abilities and cortical thickness in adolescents; single nucleotide polymorphisms that are associated with a higher risk of developing schizophrenia . Also, we recently reported that immunohistochemical localization of neuroplastin in the adult human hippocampus specifically delineates hippocampal circuitry and its principal excitatory pathways, and that there is a link between Np expression and calcium regulation in murine cortical hippocampal glutamatergic neurons . Two isoforms of neuroplastin, Np55 and brain‐specific Np65, have been described .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Np65 KO mice showed enhanced social interaction and some aspects of reduced depressive behavior as compared with the WT mice. Finally, Np65 KO mice exhibited [25] reported that Nptn ablation in glutamatergic neurons (Nptn lox/lox Emx1Cre mice) did not disturb formation of spatial memory but showed the discontinuity of swimming action with repetitive pause-swimming cycles and the swimming strategy in reversal probe test. They also reported reduced PMCAs in Nptn À/À mice, inducible Nptn KO mice and Nptn lox/lox Emx1Cre mice, which may be correlated with the altered behaviors [24,25].…”
Section: Discussionmentioning
confidence: 97%
“… reported that Nptn ablation in glutamatergic neurons (Nptn lox/lox Emx1Cre mice) did not disturb formation of spatial memory but showed the discontinuity of swimming action with repetitive pause–swimming cycles and the swimming strategy in reversal probe test. They also reported reduced PMCAs in Nptn −/− mice, inducible Nptn KO mice and Nptn lox/lox Emx1Cre mice, which may be correlated with the altered behaviors . The behavioral differences between Np65 KO and Nptn KO mice may be due to these two mouse models having different genetic deletions.…”
Section: Discussionmentioning
confidence: 99%